2003
DOI: 10.1007/s00425-003-1015-6
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of a fatty acid hydroxylase gene in developing seeds of Arabidopsis thaliana

Abstract: Expression of a cDNA encoding the castor bean ( Ricinus communis L.) oleate Delta12-hydroxylase in the developing seeds of Arabidopsis thaliana (L.) Heynh. results in the synthesis of four novel hydroxy fatty acids. These have been previously identified as ricinoleic acid (12-hydroxy-octadec- cis-9-enoic acid: 18:1-OH), densipolic acid (12-hydroxy-octadec- cis-9,15-enoic acid: 18:2-OH), lesquerolic acid (14-hydroxy-eicos- cis-11-enoic acid: 20:1-OH) and auricolic acid (14-hydroxy-eicos- cis-11,17-enoic acid: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
107
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 32 publications
4
107
2
Order By: Relevance
“…Our results with RcROD1 in different transgenic lines, along with previous reports (Smith et al, 2003;Lu et al, 2006;Burgal et al, 2008;van Erp et al, 2011), point out the complexity of the interactions among different mechanisms that channel HFAs into TAG. PDCT enhances the acyl fluxes through PC and thus reduces the pathway toward elongation outside of PC.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Our results with RcROD1 in different transgenic lines, along with previous reports (Smith et al, 2003;Lu et al, 2006;Burgal et al, 2008;van Erp et al, 2011), point out the complexity of the interactions among different mechanisms that channel HFAs into TAG. PDCT enhances the acyl fluxes through PC and thus reduces the pathway toward elongation outside of PC.…”
Section: Discussionsupporting
confidence: 80%
“…The elongation pathway is blocked in the CL37 and CL7-RcDGAT2 lines that were generated in the fae1 background. The CL37 seeds already contain 17% HFAs, which is substantially higher than the levels in the Col-FAH12 lines in this study and the lines reported previously (Smith et al, 2003). However, RcROD1 still significantly increases HFA levels in the CL37 and CL7-RcDGAT2 lines (Table II).…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Among many attempts, an alkaline pretreatment is known to efficiently remove lignin from plant cell wall structures [11]. Cellulose and hemicellulose are depolymerized to monosaccharides by synergetic actions of enzyme mixtures [12]. The most abundant monomer sugars derived from lignocellulosic biomass are D-glucose, since cellulose represents 70% of total plant cell walls, repeating the β-(1→4) glycosidic bond [13].…”
mentioning
confidence: 99%